Low serum iron is associated with anemia in CKD stage 1–4 patients with normal transferrin saturations - Pei-Hua Yu (Nature Portfolio, 2021)
Abstract Low transferrin saturation (TSAT), calculated by serum iron divided by total iron-binding capacity (TIBC), indicates iron deficiency. Because malnutrition and inflammation are associated with low TIBC in chronic kidney disease (CKD), TSAT might not reflect iron status or risk for anemia. We examined whether low serum iron was a risk factor for anemia in CKD patients with normal TSAT. Thus we compare the risk for anemia in 2500 CKD stage 1–4 patients divided by TSAT (cutoff: 20%) and serum iron (cutoff: 70 μg/dL in men, 60 μg/dL in women). Our results confirmed low TIBC (< 200 μg/dL) was associated with hypoalbuminemia and high C-reactive protein. In fully-adjusted logistic regression, both “normal TSAT low iron” and “low TSAT low iron” groups were associated with baseline anemia (hemoglobin < 11 g/dL) (odds ratios (OR) 1.56; 95% confidence interval (CI) 1.13–2.16 and OR 2.36; 95% CI 1.76–3.18, respectively) compared with the reference group (normal TSAT normal iron). Sensitivity tests with different cutoffs for TSAT and iron also showed similar results. In patients without anemia, both groups were associated with anemia after 1 year (OR 1.69; 95% CI 1.00–2.83 and OR 1.94; 95% CI 1.11–3.40, respectively). In conclusion, CKD stage 1–4 patients with normal TSAT but low serum iron are still at risk for anemia.